Chronic Alcohol Exposure Among People Living with HIV Is Associated with Innate Immune Activation and Alterations in Monocyte Phenotype and Plasma Cytokine Profile - Underwood, Michelle L.; Park, Byung; Uebelhoer, Luke S.; Gu, Geoffrey; Kunkel, Lynn E.; Korthuis, Philip T.; Cook, Ryan R.; Sekaly, Rafick Pierre; Ribeiro, Susan Pereira; Lancioni, Christina L. (Frontiers in Immunology, 2022)
Despite advances in antiretroviral therapy, chronic immune activation continues to be observed among individuals with well-controlled HIV viral loads, and is associated with non-AIDS defining morbidities among people living with HIV. Alcohol use disorder impacts a significant proportion of individuals living with HIV, and alcohol exposure is known to damage the intestinal epithelium which may increase translocation of pathogens and their molecular products, driving systemic immune activation and dysregulation. The aim of this study was to determine if adults living with HIV with well-controlled viral loads, who also suffer from alcohol use disorder with and without hepatitis C virus co-infection (n=23), exhibit evidence of advanced systemic immune activation, intestinal damage, and microbial translocation, as compared to adults living with HIV who are not exposed to chronic alcohol or other substances of abuse (n=29). The impact of a 1-month intervention to treat alcohol-use disorder was also examined. Alcohol-use disorder was associated with evidence of advanced innate immune activation, alterations in monocyte phenotype including increased expression of Toll-like receptor 4, increased burden of stimulatory ligands for Toll-like receptor 4, and alterations in plasma cytokine signature, most notably elevations in soluble CD40 ligand and transforming growth factor beta. Alcohol-associated immune activation was more pronounced among individuals with hepatitis C virus co-infection. Although the 1-month intervention to treat alcohol use disorder did not result in significant reductions in the interrogated indicators of immune activation, our findings suggest that chronic alcohol exposure is a major modifiable risk factor for chronic immune activation and dysregulation among people-living with HIV.